Corporate tax regime and international allocation of ownership - Marco Runkel; Johannes Becker (Verein für Socialpolitik, 2010)
This paper analyzes a two-country model with an international investor considering acquisitions of already existing target firms in a high-tax country and a low-tax country. The investor is able to shift profits from one location to another for tax saving purposes. Two systems of corporate taxation are compared, a system with separate accounting and a system with tax base consolidation and formula apportionment. It is shown that, under separate accounting, the number of acquisitions is inefficiently high in both the high tax and the low tax country. If a tax on acquisitions is available the high tax country will levy a positive acquisitions tax rate whereas the low tax country has no interest in doing so. Under formula apportionment, the number of acquisitions is inefficiently high in the low tax country and inefficiently low in the high tax country. The reason is that the firm has an incentive to inflate its stocks in the low tax country to reduce its effective tax rate. Now, the low tax country has an incentive to unilaterally decrease the number of acquisitions within its borders.
Keywords: H25; F23; H71; 330; Corporate Taxation; Separate Accounting; Formula Apportionment